AUSTRIA'S LAW AGAINST DEFAMATION OF RELIGION: A CASE STUDY - Taylor, Greg (Journal of law and religion, 2015)
Recently there have been calls from Islamic nations for the creation of a crime of "defamation of religion." Austria already has such an offense: section 188 of the Criminal Code of 1974 prohibits giving "justified offense" (berechtigtes Ärgernis) by "publicly disparag[ing] or ridicul[ing] a person who, or an object which, is the subject of veneration of a domestically established church or religious community, or a dogma, a lawful custom or a lawful institution of such a church or religious community." This has recently been applied to secure the conviction of an activist of the right-wing Freedom Party of Austria, who announced at a semi-public seminar attended by about thirty people, including one undercover journalist, that Mohammed was a pedophile. Drawing on the law of comparable jurisdictions, this article traces the history of the provision and considers how it is applied by the courts. In this article it is contended that this provision, while rarely used, unduly restricts public discussion. At the least, the provision needs both reinterpretation and amendment; international human rights sources suggest that repeal should be seriously considered given that the existing offense of sedition is available for serious cases.